1989
DOI: 10.1002/bip.360280141
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional 1H‐nmr study of synthetic peptides containing the main immunogenic region of the Torpedo acetylcholine receptor

Abstract: A comparative 1H-NMR spectral study of a synthetic decapeptide containing the main immunogenic region of the Torpedo acetylcholine receptor (AChR; WNPADYGGIK, representing the alpha 67-76 fragment of Torpedo AChR) with four analogous peptides (WNP3-D5YGGIK, WNPAA5YGGIK, WNPADYGGA9K, and WNPD4DYGGV9K) has been carried out in dimethyl sulfoxide. One- and two-dimensional nmr experiments [correlated spectroscopy (COSY), relayed COSY, and phase-sensitive nuclear Overhauser enhancement spectroscopy (NOESY)] were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

1991
1991
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
3
0
2
Order By: Relevance
“…The NMR experiments did not give any evidence of conformational preferences in water which strongly solvated such short peptides. In dimethylsulfoxide (DMSO), various NOEs indicated the intrinsic conformationalpreferences depending on the location of the Ala substitution in the peptide, but no correlation between the structure and the antigen-antibody hinding capacity was seen(154,155). However, usiug MIR analogs and anti-MIR mAb6, TR-NOE studies in water showed that, on binding mAb6, some ofthe analogs adopted a rigid structure, the extent of which depended on their mAb6-biuding capacity (156), The free and mAb6bound conformations of Torpedo MIR and the [A76JMIR analog have been extensively studied by NOE and TR-NOE measurements and by restrained molecular dynamics simulations based on the interproton distances deduced from the NOEs(157,158).In DMSO.…”
mentioning
confidence: 99%
“…The NMR experiments did not give any evidence of conformational preferences in water which strongly solvated such short peptides. In dimethylsulfoxide (DMSO), various NOEs indicated the intrinsic conformationalpreferences depending on the location of the Ala substitution in the peptide, but no correlation between the structure and the antigen-antibody hinding capacity was seen(154,155). However, usiug MIR analogs and anti-MIR mAb6, TR-NOE studies in water showed that, on binding mAb6, some ofthe analogs adopted a rigid structure, the extent of which depended on their mAb6-biuding capacity (156), The free and mAb6bound conformations of Torpedo MIR and the [A76JMIR analog have been extensively studied by NOE and TR-NOE measurements and by restrained molecular dynamics simulations based on the interproton distances deduced from the NOEs(157,158).In DMSO.…”
mentioning
confidence: 99%
“…Different Pro-AzAsx and AzAsx-Pro model compounds, designed for structural analysis purposes (Xaa Ala and Asx Asp or Asn) were synthesized in the liquid-phase. In order to evaluate the impact of the AzXaaaXaa substitution in a longer peptide chain, we have also prepared in the liquid-phase Boc-Trp-AzAsn-Pro-NH i Pr, an analogue of the Nterminal tripeptide sequence in the main immunogenic region (MIR Trp-Asn-Pro-Ala-Asp-Tyr-Gly-Gly-Ile-Lys) of the Torpedo californica electric organ acetylcholine receptor (AChR) which is the target in an experimental autoimmune response related to myasthenia gravis [15,16]. Triphosgene was also used for the solid-phase synthesis of two azaanalogues of the MIR decapeptide containing either AzAsn 2 or AzAla 4 .…”
mentioning
confidence: 99%
“…Anti-MIR mAb binding has been gradually localized between amino acid residues 1-151 (Barkas et al, 1986), 46-120 (Ratnam et al, 1986), 37-85 (Barkas et al, 1987), 61-76 (Barkas et al, 1988) 67-78 (Wood et al, 1989 and finally 67-76 of the AChR ol-subunit . The conformation of the MIR decapeptide, either free (in dimethyl sulfoxide) or bound on the corresponding anti-MIR mAb, has been elucidated by the use of two-dimensional NMR experiments (Cung et al, 1989(Cung et al, , 1992. Interestingly, Sano et al (1991), by mapping antibodies raised against a recombinant human muscle AChR a-subunit domain (a1 -210), using human a-subunit peptides, showed that the sequence around a65 -72 (i. e. that strongly overlaps with the MIR decapeptide a67 -76) is very antigenic in rats, mice and rabbits.…”
mentioning
confidence: 99%